Coronary Artery Spasm and Perivascular Adipose Tissue Inflammation: Insights From Translational Imaging Research - Kazuma Ohyama (Radcliffe Medical Media, 2019)
Perivascular adipose tissue, which constitutes perivascular components along with the adventitial vasa vasorum, plays an important role as a source of various inflammatory mediators in cardiovascular disease. Inflammatory changes in the coronary adventitia are thought to be involved in the pathogenesis of coronary artery spasm and vasospastic angina. Recent advances in translational research using non- invasive imaging modalities, including 18F-fluorodeoxyglucose PET and cardiac CT, have enabled us to visualise perivascular inflammation in the pathogenesis of coronary artery spasm. These modality approaches appear to be clinically useful as a non-invasive tool for examining the presence and severity of vasospastic angina.